The Task and the Scope of the Science of Human Action – Part I:: The Nature and Development of the Social Sciences - Mises, Ludwig von (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2015)
The author examines the objectives and the appropriate method for developing research in the field of the social sciences, discussing the origin of these sciences and covering, with particular attention, the fields of economics and sociology. Elaborating a critical stance against both historicism and empiricism, the author argues in favor of a universal science – praxeology, or the science of human action.